Evidence Based Practice:Perspectives of Iranian Urologists - hajebrahimi, sakineh; Sadeghi-Ghyassi, Fatemeh; Olfati, Nahid; Dastgiri, Saeed; Maghbouli, Leili (Urology Journal, 2014)
Abstract Purpose: To determine the attitudes and beliefs of Iranian urologists toward Evidence Based Medicine (EBM) and investigation of the barriers of evidence based practice (EBP). Materials and Methods: A self- administrated, Likert scale questionnaire designed in Persian and filled up by censuses selected urologist from Iranian Urology Association (IUA). Data were entered to Predictive Analytics Soft Ware version 18.0 and descriptive statistics were obtained for all parts of the questionnaire. Results: A total of 111 out of 500 Iranian urologists who attended in IUA annual meeting, responded to the questionnaires. Mean attitude score of respondents was 30.4 (SD: 5.7, range 16-40). Attitude score showed statistically significant association to previous participation in EBM workshops (P = .01). Of participants 96% believed EBP will improve patient care and 76.2% of them appreciated the impact of use of research utilization and application of evidence based guidelines on clinical decision making and the outcome of surgery. The main barriers to EBP stated as lack of time (64.8%), facilities (53.4%), and training in EBM (29.4%). Conclusion: The urologists have positive attitudes towards EBP. However, regarding lack of time, pre-appraised databases or EBP guidelines can be helpful. Evidence based workshops and familiarity with evidence databases is recommended for Iranian urologists. In addition, health care system and policy makers could play a major role to provide a culture of EBP.